Conocimientos, actitudes y prácticas en detección del cáncer cervicouterino en pacientes con virus inmunodeficiencia humana, Hospital Regional de Loreto, 2022 - Quintana Ruiz, Raúl Alejandro (2022)
In the Loreto region of patients living with HIV, 73.3% are concentrated in Iquitos. Patients with HIV have a higher risk of acquiring infections by high-risk HPV types for cervical cancer, screening being an early detection measure, however, the detection of cervical cancer is low. Being one of the main detection barriers, the lack of knowledge. The present investigation had as objectives to evaluate the knowledge, attitudes and practices of women infected with HIV for the detection of cervical cancer in the HRL, 2022. The study is observational of cross-sectional type, which included as a population woman patient older than 18 years old attending the HRL HIV program. 197 patients were included, with a mean age of 36.9 years. 48.3% did not complete the basic education level, 68% are unemployed, 53.8% have a low socioeconomic level, and 58.4% have started their sexual activities as a minor. Origin, education level, marital status, and counseling were significantly associated with level of knowledge. HIV diagnosis time and CD4 levels were significantly associated with attitude levels. Age, occupation, marital status, having received counseling, CD4 levels, number of sexual partners, and time since HIV diagnosis were significantly associated with levels of practice.